Hyperoxia does not directly affect vascular tone in isolated arteries from mice. - B Smit; Y M Smulders; M C de Waard; H M Oudemans-van Straaten; A R J Girbes; E C Eringa; A M E Spoelstra-de Man (PLoS ONE)
Hospitalized patients often receive oxygen supplementation, which can lead to a supraphysiological oxygen tension (hyperoxia). Hyperoxia can have hemodynamic effects, including an increase in systemic vascular resistance. This increase suggests hyperoxia-induced vasoconstriction, yet reported direct effects of hyperoxia on vessel tone have been inconsistent. Furthermore, hyperoxia-induced changes in vessel diameter have not been studied in mice, currently the most used mammal model of disease. In this study we set out to develop a pressure-myograph model using isolated vessels from mice for investigation of pathways involved in hyperoxic vasoconstriction. Isolated conduit and resistance arteries (femoral artery and gracilis arteriole, respectively) from C57BL/6 mice were exposed to normoxia (PO2 of 80 mmHg) and three levels of hyperoxia (PO2 of 215, 375 and 665 mmHg) in a no-flow pressure myograph setup. Under the different PO2 levels, dose-response agonist induced endothelium-dependent vasodilation (acetylcholine, arachidonic acid), endothelium-independent vasodilation (s-nitroprusside), as well as vasoconstriction (norepinephrine, prostaglandin F2α) were examined. The investigated arteries did not respond to oxygen by a change in vascular tone. In the dose-response studies, maximal responses and EC50 values to any of the aforementioned agonists were not affected by hyperoxia either. We conclude that arteries and arterioles from healthy mice are not intrinsically sensitive to hyperoxic conditions. The present ex-vivo model is therefore not suitable for further research into mechanisms of hyperoxic vasoconstriction.